PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTU APLIKASI GOOGLE MY MAPS TERHADAP MINAT BELAJAR GEOGRAFI KELAS XII SMA PERTIWI 1 PADANG - Nafrio, Ahmad; Suasti, Yurni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low interest in learning geography among twelfth-grade students at SMA Pertiwi 1 Padang, particularly in the topic of Geographic Information Systems (GIS), is caused by the conventional learning process, which mainly relies on PowerPoint presentations and lectures. Ideally, GIS learning should emphasize practical activities and the application of concepts. However, limited facilities and infrastructure, such as the availability of computers and teachers’ ability to operate GIS applications, have hindered the optimal implementation of practical learning. To address this issue, this study introduces a solution through the application of the Project Based Learning (PjBL) model assisted by the Google My Maps application. This web-based application can be accessed via mobile phones, enabling students to experience how GIS works in practice. The research employed a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The findings indicate that students’ learning interest significantly improved when using the PjBL model assisted by Google My Maps in GIS learning. This is supported by the hypothesis testing results, showing a significance value (2-tailed) of 0.006 < 0.05, which means that H₁ is accepted and H₀ is rejected. Therefore, the PjBL model assisted by Google My Maps is proven to be effective in increasing students’ learning interest compared to the conventional learning model.